Bone mass, depressive and anxiety symptoms in adolescent girls: Variation by smoking and alcohol use - Dorn, L.D. (2011)
PURPOSE: The purpose of the study was to examine (a) the association between depressive and anxiety symptoms with bone health, (b) the association of smoking or alcohol use with bone health, and, in turn, (c) whether the association between depressive and anxiety symptoms with bone health varied by smoking or alcohol use individually or by combined use. Bone health included total body bone mineral content (TB BMC) and bone mineral density (BMD) of the lumbar spine, total hip, and femoral neck. Previous literature has not examined these issues in adolescence, a time when more than 50% of bone mass is accrued. METHODS: An observational study enrolled 262 healthy adolescent girls by age cohort (11, 13, 15, and 17 years). Participants completed questionnaires and interviews on substance use, depressive symptoms, and anxiety. BMC and BMD were measured by dual energy x-ray absorptiometry. RESULTS: Higher depressive symptoms were associated with lower TB BMC and BMD (total hip, femoral neck). Those with the lowest level of smoking had higher BMD of the hip and femoral neck whereas no differences were noted by alcohol use. Regular users of both cigarettes and alcohol demonstrated a stronger negative association between depressive symptoms and TB BMC compared with non-users/experimental users and regular alcohol users. Findings were parallel for anxiety symptoms. CONCLUSION: Depressive and anxiety symptoms may negatively influence bone health in adolescent girls. Consideration of multiple substances, rather than cigarettes or alcohol separately, may be particularly informative with respect to the association of depression with bone health.